Consumption of Sugar-Sweetened Beverages and Artificially Sweetened Beverages with Mortality: The National Health and Nutrition Examination Survey and a Meta-Analysis - Zhang, Yan-Bo (Curr Dev Nutr, 2020)
OBJECTIVES: We aimed to investigate the associations of dietary intakes of sugar-sweetened beverages (SSB) and artificially sweetened beverages (ASB) with mortality. METHODS: Adults without cancer aged 20 years or older from the National Health and Nutrition Examination Survey 1999–2014 were followed up to December 31, 2015. Beverage intake was assessed by 24-hour dietary recall interviews (a single recall in 5109 participants and an average of two recalls in 19,914 participants). Multivariable Cox proportional hazards models were used to evaluate the associations of SSB and ASB intake with all-cause and cause-specific mortality. Pubmed, Embase, Web of Science, Cochrane, ProQuest, ClinicalTrials.gov, and International Clinical Trials Registry Platform were searched for related cohort studies. Random-effects models were used to pool the estimates, and dose-response analyses were conducted using the 2-stage generalized least-squares trend program. RESULTS: After a median follow-up of 6.8 years, 2365 deaths were identified in 25,023 participants. Each additional serving of daily SSB intake was associated with an HR (95% CI) of 1.06 (1.02–1.11), 1.13 (1.03–1.24), and 1.06 (1.00–1.11) for mortality from all-cause, heart diseases, and other causes. Each additional serving of daily ASB intake was associated with an HR (95% CI) of 0.96 (0.92–1.00), 0.90 (0.82–0.98), and 0.97 (0.92–1.02) for mortality from all-cause, heart diseases, and other causes. No significant associations were found with cancer mortality. We identified 23,631 citations and included 12 studies (including 13 cohorts) in meta-analyses. It was shown that each additional serving of daily SSB intake was associated with an HR (95% CI) of 1.08 (1.05–1.11, ten cohorts with 388,548 participants) for all-cause mortality and 1.10 (1.06–1.14, five cohorts with 255,584 participants) for cardiovascular mortality. No significant association was found between ASB intake and mortality in the meta-analysis. CONCLUSIONS: Higher SSB intake was associated with a higher risk of all-cause mortality and cardiovascular mortality, while the association between ASB intake and mortality needed further investigation. FUNDING SOURCES: National Key Research and Development Program of China, National Nature Science Foundation of China, and Hubei Province Science Fund for Distinguished Young Scholars.